2022
DOI: 10.1097/prs.0000000000008985
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Oncoplastic Reduction Has on Long-Term Recurrence in Breast Conservation Therapy

Abstract: Background: The use of oncoplastic reduction techniques have many proven benefits over lumpectomy alone in the management of women with breast cancer. The impact it has on tumor recurrence is unclear. The purpose of this review was to evaluate the incidence of recurrence in patients who underwent oncoplastic reduction techniques compared to lumpectomy alone. Methods: A prospectively maintained database of patients at Emory Hospital who underwent oncoplastic reduction techniques at the time of tumor resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Of note, both studies also noted higher risk tumors in the OPS group, suggesting that the oncoplastic approach extends indications for BCT in more aggressive disease with similar recurrence rates 11,12 . A recent review and metanalysis of 31 studies further support this data, noting lower LRR rates in OPS groups when compared to standard BCS 13 …”
Section: Oncologic Safety and Outcomesmentioning
confidence: 81%
See 1 more Smart Citation
“…Of note, both studies also noted higher risk tumors in the OPS group, suggesting that the oncoplastic approach extends indications for BCT in more aggressive disease with similar recurrence rates 11,12 . A recent review and metanalysis of 31 studies further support this data, noting lower LRR rates in OPS groups when compared to standard BCS 13 …”
Section: Oncologic Safety and Outcomesmentioning
confidence: 81%
“…11,12 A recent review and metanalysis of 31 studies further support this data, noting lower LRR rates in OPS groups when compared to standard BCS. 13…”
Section: Recurrence Riskmentioning
confidence: 99%
“… 18 , 19 As for the issue of oncologic recurrence, a previous study from our institution found equivalent long-term recurrence rates between surgical techniques. 20 …”
Section: Discussionmentioning
confidence: 99%
“…18,19 As for the issue of oncologic recurrence, a previous study from our institution found equivalent long-term recurrence rates between surgical techniques. 20 The discussion of delay in radiation after reconstructive breast modalities also extends to procedures such as mastectomy with immediate breast reconstruction. One study by Shammas et al found that despite a modest delay in initiation of radiation therapy after immediate breast reconstruction, the delay did not impact overall survival.…”
mentioning
confidence: 99%
“…Since the introduction of lumpectomy during the 90s, breast-conserving surgery (BCS) followed by whole breast irradiation has been demonstrated to be safe and comparable to mastectomy in terms of local recurrences [70,71].…”
Section: The Rationale Of Margins Evaluationmentioning
confidence: 99%